Tuberculosis Expanding Knowledge - Ribon, Wellman (IntechOpen, 2015)
Progress obtained by mycobacteriology in recent years is undeniable with regards to preventing, detecting, and treating cases of tuberculosis, millennial disease that is still present as public health issue worldwide. We present here high-impact research and interest topics related to the application of new methodologies, especially molecular methods for rapid diagnostic such as rapid DST, application of high performance liquid chromatography, molecular epidemiology and molecular diagnostic testing on post mortem. Currently, the constant search for vaccines that prevent the disease is promising through research of the immune response generated by the host towards the bacterium, and the effectiveness that may be achieved from developed vaccines. Another high-impact factor is the one generated by considering tuberculosis as a social disease with an infectious component reflected in research about tuberculosis and human rights. Finally, we present important issues of the pathogen interaction with different hosts. The constant knowledge generation that expands the frontiers of understanding is a key factor for finding solutions and successful activities for public health.